Midwifery-led brief counseling on the severity of posttraumatic stress symptoms of postpartum hemorrhage: quasi-experimental study - Seyedeh Shohreh Sajedi; Shahin-Dokht N; Ali Navidian (BMC, 2024)
Abstract Background Postpartum hemorrhage is a preventable cause of maternal mortality all over the world and a significant contributor to post-traumatic stress among women. Methods This quasi-experimental study was conducted in 2023 on 60 primiparous women with postpartum hemorrhage in Zahedan, Iran. The participants were identified and randomly assigned to two groups. The intervention group received face-to-face individual counseling based on Gamble's counseling model, conducted by a midwife. The counseling lasted from 40 to 60 min and took place over two sessions; one within the first 48 to 72 h in the ward, and a follow-up telephone session two weeks postpartum. Assessments were made using the Post-Traumatic Stress Disorder (PTSD) Checklist for DSM-5 (PCL-5) and the Perinatal Post-Traumatic Stress Disorder Questionnaire-II (PPQ-II) before the intervention and four weeks after the last post-test session for the two groups, either in person or by phone. Results Following the intervention, the post-traumatic stress score (PCL-5) in the intervention group significantly decreased compared to the control group (P < 0.001). Moreover, the perinatal post-traumatic stress disorder score (PPQ-II) after midwife-led brief counseling in the intervention group was significantly lower than in the control group, as determined by an analysis of covariance (ANCOVA), controlling for pre-test effects (p =0.05). Conclusions Midwife-led brief counseling may be effectively implemented by developing a localized clinical guideline based on midwifery recommendations following traumatic births caused by postpartum hemorrhage.